Exploration of Factors Influencing Students’ English Speaking - Musurmonova Robiya Jahongir qizi (Zien Journals, 2022)
The article describes an approach to teaching oral speech in English to students of the direction of training future teachers of English, taking into account the specifics of their future professional activities. The expediency of the method of modeling speech situations, substitution and reproductive exercises at an early stage of formation of foreign language communicative competence of students is substantiated. The necessity of phased work with audio or video materials is emphasized, followed by the compilation of speech samples from them for the development of speaking skills. The author comes to the conclusion that these methods help students overcome the language barrier and avoid mistakes when creating their own prepared statements in professionally demanded genres.
Keywords: Speaking; ability; methods; operate